2016
DOI: 10.1016/j.actbio.2016.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent behaviors of bone marrow derived mesenchymal stem cells and infectious bacteria toward magnesium oxide nanoparticles

Abstract: This article reports the quantitative relationship between the concentration of magnesium oxide (MgO) nanoparticles and its distinct biological activities towards mammalian cells and infectious bacteria for the first time. The effects of MgO nanoparticles on the viability of bone marrow derived mesenchymal stem cells (BMSCs) and infectious bacteria (both gram-negative Escherichia coli and gram-positive Staphylococcus epidermidis) showed a concentration-dependent behavior in vitro. The critical concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 42 publications
5
86
1
Order By: Relevance
“…In addition, MNMS nanosheets released the ROS, which is highly stabilized in basic solution . However, these ROS are the main factors in the bactericidal action of MNMSs nanosheets, causing cytotoxic effect of MNMSs against pathogenic microbes …”
Section: Resultsmentioning
confidence: 99%
“…In addition, MNMS nanosheets released the ROS, which is highly stabilized in basic solution . However, these ROS are the main factors in the bactericidal action of MNMSs nanosheets, causing cytotoxic effect of MNMSs against pathogenic microbes …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies into Mg-containing nanomaterials include MgONPs for orthopedic implant coating and fabrication of MgO-containing nanocomposites as scaffolds for bone tissue regeneration. Wetteland et al 143 report possible guidelines for MgONP-coated biomaterial design. The study showed a significant increase in bone marrowderived mesenchymal stem cells and antibacterial activity when exposed to 200 µg/mL of MgONPs.…”
mentioning
confidence: 99%
“…), and thus increased its direct contact with BMSCs. The nMgO nanoparticles were previously reported to increase BMSC adhesion and proliferation at a low concentration of 200 µg/mL and induced the death of BMSCs at the concentrations >500 µg/mL . This indicated possible cytotoxicity of nMgO at higher concentrations, especially when nMgO was in direct contact with cells.…”
Section: Discussionmentioning
confidence: 92%
“…The nMgO nanoparticles were previously reported to increase BMSC adhesion and proliferation at a low concentration of 200 μg/mL and induced the death of BMSCs at the concentrations >500 μg/mL. 15 This indicated possible cytotoxicity of nMgO at higher concentrations, especially when nMgO was in direct contact with cells. The nMgO/PLGA_A increased cell density at the first 24 h of culture likely because agglomeration reduced direct contact of nMgO with BMSCs and the concentration of nMgO on the top surface was at a low level beneficial to cells.…”
Section: Optical Properties Of the Nanocomposites With Dispersed Versmentioning
confidence: 93%
See 1 more Smart Citation